Prompt books from the Folger Shakespeare Library, Washington, D.C. : basic documentary sources concerning text and performance - Shakespeare, William, 1564-1616 (Britain's literary heritage. Shakespeare and the stage, 1930)
Prompt books for all of Shakespeare's plays except Titus Andronicus. The materials range from complete revisions of plays to copies with the direction of entrances and exits shown. Also included are materials on lighting, costumes, music, etc., and printed souvenir books. The 19th century collection is particularly strong.